RED BLOOD CELL TRANSFUSION IN PATIENTS WITH PLACENTA ACCRETA SPECTRUM : A SYSTEMATIC REVIEW - Fahrozy, Akhmad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Placenta accreta spectrum, formerly known as morbidly adherent placenta, refers to the range of pathologic adherence of the placenta, including placenta increta, placenta percreta, and placenta accreta. Maternal morbidity and mortality can occur because of severe and sometimes life-threatening hemorrhage, which often requires blood transfusion. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 32 articles, whereas the results of our search on SagePub brought up 25 articles. The results of the search conducted for the last year of 2013 yielded a total 32 articles for PubMed and 3 articles for SagePub. In the end, we compiled a total of 3 papers, 2 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: Based on the studies included in this review, we are unable to recommend the minimum of units of red blood cells that should be available before delivery for patients with placenta accreta spectrum. Future studies in the form of large clinical trials is required to study the minimum of RBCs units for PAS patients before delivery, to better inform future guidelines for predelivery blood ordering and transfusion support.